Hetero‐Functional Polymers with Alternating Hydroxyl and Epoxy Groups Synthesized by Thiol‐yne Click (co)Polymerization. Issue 20 (21st September 2018) - Zheng, Yaochen; Zhang, Qian; Gao, Zhengguo; Li, Fucun; Yan, Bingfei; Li, Wenzuo
Abstract: A new family of hetero‐functional polythioethers with alternating hydroxyl and epoxy groups are facilely synthesized via photo‐initiated thiol‐yne click (co)polymerization under mild reaction conditions. Their chemical structures and hetero‐functional group density can be finely tuned by adjusting the feeding mole ratios. As the evidence of nuclear magnetic resonance and gel permeation chromatography tests shows, either the molecular weight or the hetero‐functional group density depend greatly on the SH bond cleavage energy of dithiols which can be predicted by theoretical calculation, using the density functional theory (DFT) with B3LYP hybrid functional and the QCISD methods. This paper provides access to a wide range of new materials with a specific structure and plentiful alternating hetero‐functional groups. Moreover, it unveils and highlights the role of SH bond cleavage energy of dithiols during the process of step‐growth thiol‐yne click (co)polymerization. Abstract : Hetero‐functional polymers with alternating hydroxyl and epoxy group are facilely synthesized via thiol‐yne click (co)polymerization. The density of groups depends greatly on the SH bond cleavage energy and can be tunable through adjusting the feeding mole ratio of comonomers. This work provides access to a wide range of new materials with a specific structure and plentiful alternating hetero‐functional groups.